Considerations on the surgical treatment of the spleen - Perrier, José (Cirugía del Uruguay, 1986)
The surgical-therapeutic conduct with the spleen is discussed in the light of new studies on the risks accompanying splenectomy, sudden sepsis in particular. Analysis of difieren! splenectomy indications in local medicine on the basis of 347 splenectomies performed at the Hospital de Clínicas in ten years (1972-1982). Accordingly, an interventionist action is proposed in case of spleen rupture, with a view to, as far as _posible, preserving the organ. Pointed out is !he importance of preventing and avoiding splenectomies by surgical iatrogeny and finally, the precautions to be taken when extirpation of the spleen es necessary.